Cruise tourism in Malaysia: A SWOT Analysis - Chong, Daniel Ka Leong * (2015)
According to Tourism Malaysia, the Asian and international cruise in growing at the average of 14% annually over the past ten years while number of cruise passengers in Malaysia also expected to exceed half a million in 2013. Despite its potential, the cruise industry in Malaysia is facing ever-growing of competitions from their neighboring countries. An SWOT Analysis was used to discuss the potential of improving strategic decision and planning for cruise tourism in Malaysia. According to findings, notable strengths include a growing market and the government’s push to upgrade ports’ infrastructure. Weaknesses include oligopolistic competition and negative perception of Malaysian cruises being overly gambling-oriented rather than holiday making. Opportunities are seen in three areas: 1) Increase of spending in travel and cruising; 2) Exemption from the Malaysia Cabotage Policy was given to all international cruises by the Malaysian government, hence, attracting more international cruises to stopover to more destinations in Malaysia; 3) Strong supports from Malaysian government, as well as their initiatives to concern, and develop this business now and future. Piracy and safety have been identified as the main threats that create risks for the cruise business in Malaysia.